PERNIKAHAN NABI MUHAMMAD SAW (ANALISIS HISTORI DAN SOSIOLOGIS) - Anis, Anis; Sulfikar K (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2025)
Prophet Muhammad SAW is a central figure in Islamic teachings who is seen as a perfect human being and a role model for humanity. However, in Western orientalist and Islamological studies, the personal life of the Prophet SAW, especially regarding his marriages with several women, is often highlighted negatively. Accusations such as pedophilia in his marriage to Aisha RA and the assumption of being sexually insane due to the practice of polygamy are issues that are often raised without understanding the historical and sociological context behind it. The purpose of this study is to find out the history and explain the motives of Prophet Muhammad's marriage and to determine and discuss the social implications of Prophet Muhammad's marriage. This study uses a qualitative method with a library research approach. Data is obtained through a literature review from various sources, both primary and secondary, related to the topic. In addition, historical methods are used which include heuristics, source criticism, interpretation, and historiography. Historical and sociological approaches are used to examine the Prophet's marriage. The results of the study show that the marriage of Prophet Muhammad SAW cannot be understood as a purely personal matter, but rather as part of a prophetic mission that encompasses social, legal, educational, and spiritual dimensions. Each marriage carries contextual and universal wisdom, and aims to protect vulnerable groups and strengthen Islamic values. From a sociological perspective, marriage is a strategy for social transformation from a tribal system to an inclusive society based on the principles of justice and togetherness in Islam